INFLUENCE OF OPTIC NERVE DRUSEN ON VISUAL FUNCTIONS IN CHILDREN AND ADOLESCENTS WITH ESSENTIAL ARTERIAL HYPERTENSION - A. G. Shchuko (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
The article presents data examination of children and male adolescents, aged 8 to 17 years without eye pathologies, with primary hypertension diagnosis - established at the clinic of Scientific Centre for Family Health and Human Reproduction Problems. Examination results were: 42 patients (84 eyes) had primary hypertension with optic disc drusen, 8 patients (16 eyes) had primary hypertension without optic disc drusen. Characteristics of basic functional changes of patients ophthalmic status with and without optic disc drusen on the basis of data of visometry refractometry, keratometry, computer perimetry, ultrasonic ehobiometry. Doppler angiographic examination of ocular vessels, electroretinography (ERG) according to registration standards proposed by the International Society of Clinical electrophysiology of (ISCEV), visual-evoked potentials (VEP), biomicroscopy of the eye, fundus photo registration. To verify and differentiate the prominence of the optic disc drusen in cases of the prominence of stagnant disc with characteristic extension of perineural space, all patients underwent an ultrasound scan procedure of the eyeball. The study obtained data on early pre-clinical manifestations of hypertensive angiohorioretinopaty. The risk factors for the formation of drusen of the optic nerve were identified. We determined that the presence of drusen does not lead to the aggravation of the changes of the visual system, formed under the influence of high blood pressure, affecting only the indicators characterizing ischemic processes in the retina and the optic nerve, which is due to the influence of compression of drusen on glial tissue and the vascular wall.